KONTRIBUSI EDUCATION CANNOT WAIT (ECW) DALAM PEMULIHAN PENDIDIKAN DI SURIAH - Safitri, Desy; Sassi, Komarudin (LPPM UM Metro, 2024)
AbstractThe armed conflict in Syria has caused a severe humanitarian crisis, including significant disruption of the education system. Education, as a basic human right, is key in rebuilding post-conflict countries and societies. In this context, the role of Education Cannot Wait (ECW) as a global humanitarian foundation for education in emergencies becomes very crucial. This research aims to analyze ECW's contribution to efforts to restore education in Syria. Through a qualitative approach, this research will examine various programs and initiatives that have been implemented by ECW in Syria. Data will be collected through literature studies. It is hoped that the research results will provide a comprehensive picture of the extent to which ECW has been successful in overcoming the challenges of educational recovery in Syria. Apart from that, it is also hoped that this research can provide policy recommendations for policy makers, humanitarian organizations and other stakeholders in an effort to increase the effectiveness of humanitarian assistance in the education sector in the future. Keywords: Education Cannot Wait, Syria, education recovery, humanitarian crisis, humanitarian aid AbstrakKonflik bersenjata di Suriah telah menyebabkan krisis kemanusiaan yang parah, termasuk disrupsi sistem pendidikan yang signifikan. Pendidikan, sebagai hak dasar manusia, menjadi kunci dalam membangun kembali negara dan masyarakat pasca-konflik. Dalam konteks ini, peran Education Cannot Wait (ECW) sebagai fondasi kemanusiaan global untuk pendidikan dalam keadaan darurat menjadi sangat krusial. Penelitian ini bertujuan untuk menganalisis kontribusi ECW dalam upaya pemulihan pendidikan di Suriah. Melalui pendekatan kualitatif, penelitian ini akan mengkaji berbagai program dan inisiatif yang telah dilaksanakan oleh ECW di Suriah. Data akan dikumpulkan melalui studi literatur. Hasil penelitian diharapkan dapat memberikan gambaran yang komprehensif mengenai sejauh mana ECW berhasil dalam mengatasi tantangan-tantangan dalam pemulihan pendidikan di Suriah. Selain itu, penelitian ini juga diharapkan dapat memberikan rekomendasi kebijakan bagi para pembuat kebijakan, organisasi kemanusiaan, dan para pemangku kepentingan lainnya dalam upaya meningkatkan efektivitas bantuan kemanusiaan di bidang pendidikan di masa depan. Kata Kunci: Education Cannot Wait, Suriah, Pemulihan Pendidikan, Krisis Kemanusiaan, Bantuan Kemanusiaan.